UPAYA INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENYEDIAKAN PENDIDIKAN ANAK-ANAK PENGUNGSI INTERNASIONAL DI INDONESIA MELALUI PROGRAM MIGRANT ASSISTANCE PERIODE 2018-2022 - Vashaya Alinda Syadina (2023)
Prolonged conflicts that occurred in various countries in various parts of the world led to the emergence of refugee flows in the world. Refugees leave their country and try to find a better life in another country. In the process, refugees must face various challenges, one of which is not fulfilling the education of refugee children in accordance with the human rights they have. In responding to this, Indonesia as a transit country cooperates with one of the IGOs in the world, IOM, in providing education for international refugee children in Indonesia. IOM as a leading international organization engaged in immigration has been trusted by the government to help deal with various refugee problems in Indonesia through its policies. Migrant Assistance as one of IOM's work programs allows international refugee children in Indonesia to receive formal education while waiting for their citizenship status in a third country. However, with the large number of refugees in Indonesia, IOM has limitations so that it cannot cover all refugees which causes independent refugees to emerge. If the two are compared, IOM has succeeded in carrying out its duties because it can provide a prosperous life for the refugees under its auspices.